2022
DOI: 10.3389/fphys.2022.972041
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of in ovo feeding of low or high mixtures of cysteine and lysine on performance, intestinal morphology and physiological responses of thermal-challenged broiler embryos

Abstract: The objective of this study was to evaluate the effect of in ovo feeding cysteine, lysine or their combinations on the perinatal and post-hatch physiological responses of broiler embryos exposed to heat stress during incubation. A total of two thousand fertile eggs of broiler breeders (Ross 308) flock (at 38 weeks of age) were used for this study. In the first 10 days, the eggs were incubated using the conventional protocol of relative humidity and temperature of 55% and 37.8°C respectively. From day ten onwar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 63 publications
0
16
0
Order By: Relevance
“…Cysteine effectively protects the physical barrier of the intestine. For instance, cysteine protects the intestine of broiler chicks by increasing the length of the intestinal villi ( 51 ). In addition, cysteine has been found to improve intestinal integrity and permeability and reduce the intestinal inflammatory response in pigs ( 25 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cysteine effectively protects the physical barrier of the intestine. For instance, cysteine protects the intestine of broiler chicks by increasing the length of the intestinal villi ( 51 ). In addition, cysteine has been found to improve intestinal integrity and permeability and reduce the intestinal inflammatory response in pigs ( 25 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Gonzales et al (2022) revealed that IOF of a combination of sulphur amino acids (5.90 mg of l-methionine and 3.40 mg of l-cysteine) plus 0.15 mg of folic acid increased the ileal crypt depth in neonatal chicks. Also, Ajayi et al (2022) demonstrated that IOF of a blend of 3.4 mg cysteine + 2 mg lysine on day 17.5 of incubation improved intestinal morphology, including elevated duodenal villus height, villus surface area, and villus height/crypt depth ratio. These results confirmed the previous studies, which showed that IOF of lysine enhanced the intestinal histomorphology in pigeons (Zhu et al 2019).…”
Section: Impact Of In Ovo Feeding On Digestive System Development And...mentioning
confidence: 91%
“…Han et al (2022) postulated that IOF of l-leucine (69 μmol) increased serum GSH-Px and decreased serum MDA concentrations of broilers at 39 days of age. Also, Ajayi et al (2022) demonstrated that IOF of a mixture of 3.4 mg cysteine + 2 mg lysine on day 17.5 of incubation increased serum SOD and decreased serum MDA concentrations of dayold chicks. Additionally, Lu et al (2022) proved that IOF of 1% l-arginine on day 18 of incubation increased total antioxidant capacity and reduced MDA content of breast muscle at 21 days of age.…”
Section: Impact Of In Ovo Feeding Of Nutraceuticals On Antioxidative ...mentioning
confidence: 92%
See 2 more Smart Citations